On the stabilization problems of non-holonomic systems with inhomogeneous constraints with incomplete information on the state - A.Ya., Krasinskiy; E M, Krasinskaya (International Journal of Engineering and Technology, 2018)
TheÂ systematic application of Voronetz vector-matrix equations in Routh variables is developed to describe the dynamics of non-holonomic systems with inhomogeneous constraints. The obtained form of the equations of disturbed motion in problems of stability and stabilization makes it possible to analyze the structure of the model for a reasonable choice of the application of control actions. The developed technique makes it possible to automate the solution of problems of stabilization of operating modes of complex technical devices.